Evaluation of effectiveness and safety of a herbal compound in primary insomnia symptoms and sleep disturbances not related to medical or psychiatric causes - Palmieri G (Dove Medical Press, 2017)
Giancarlo Palmieri,1,2 Paola Contaldi,1 Giuseppe Fogliame1 1ANARDI Medical and Scientific Association, Scafati, Italy; 2Department of Internal Medicine, Niguarda Cà Granda Hospital, Milan, Italy Background and purpose: Sleep disturbances and related daytime activities impairment are common diseases nowadays. General practitioners are often the first health care professional asked to alleviate sleep disturbances and primary insomnia symptoms. Beyond a wide class of hypnotic drugs, botanicals can represent an alternative treatment for those kinds of symptoms. The scope of the present study is to evaluate safety and effectiveness of a herbal compound composed of valerian, hop, and jujube (Vagonotte®) on primary insomnia symptoms and sleep disturbances not related to medical or psychiatric causes.Patients and methods: One hundred and twenty subjects with sleep disturbances symptoms were randomized in two branches of 60 persons each, receiving the herbal compound or placebo at dosage of two pills per day 30 minutes before their scheduled bedtime. All subjects were screened for precise items related to sleep quality and daytime activity at the beginning, after 10 days, and after 20 days of consecutive dietary supplement (or placebo) consumption. The participants remained blind to group assignment until all of them completed the trial.Results: Sleep onset, numbers of nocturnal awakenings, and overall nocturnal slept time were assessed. A statistically significant difference between the two groups emerged. The group receiving the herbal compound showed a lower time of sleep onset compared to placebo group, the same result was obtained for total slept time and night awakenings frequency (p<0.001). Daily symptom improvement in subjects receiving the herbal compound showed significant reduction in tension and irritability, difficulty in concentration, and fatigue intensity, if compared to placebo scores (p<0.001). None of the 60 subjects in the verum group reported adverse reaction related to the herbal compound, and 98% of subjects judged the product as having from good to excellent safety and tolerability.Conclusion: Botanicals dietary supplement with relaxing and soothing properties can help practitioner to treat primary insomnia, especially when the risk/benefit profile of a patient does not sustain hypnotic drugs prescription. This clinical investigation on safety and effectiveness of a herbal compound made of valerian, hop, and jujube opens interesting perspectives on usage of herbal compound to manage primary insomnia. Further investigations could help in understanding herbal compounds’ effectiveness on sleep disturbances. Keywords: insomnia, sleep disturbance, fatigue, tension